TRANSCENDING NEW PUBLIC MANAGEMENT - TOM CHRISTENSEN PER LÆGREID , PER LÆGREID (Tom Christensen and Per Lægreid, 2007)
This book contains studies focusing on post-New Public Management (NPM) reforms by contrasting them with the NPM-based public-sector reforms that took place during the last two decades of the twentieth century. Its empirical focus is on Australia, Denmark, Norway, New Zealand and Sweden. Our theoretical approach is a transformative one, embracing political design, cultural–institutional trajectories and external pressure to understand the processes and effects of the reforms. A main aim of our study is to examine what has happened over time. We look beyond NPM and a central question being asked is whether NPM is finished. Our argument is that NPM is by no means over. It has, however, been challenged. New types of reforms have been added, and there have been some reversals, especially when it comes to the disaggregation components of NPM. We also see a reassertion of the centre, strengthening of central policy capacity and whole-of-government initiatives to enhance horizontal co-ordination. There are a number of individuals and organizations to whom we owe our thanks. An acknowledgement goes to our network of colleagues and friends who share an interest in institutional change, comparative public administration and public-sector reform. This book is a follow-up to our 2001 volume (Tom Christensen and Per Lægreid (eds), New Public Management. The Transformation of Ideas and Practice, Aldershot: Ashgate). Special thanks go to our hosts at the Centre for Research in Public Sector Management at the University of Canberra and at the School of Business and Public Management at Victoria University of Wellington. Thanks are also due to Hilde Kjerland for technical assistance in supervising the preparation of the manuscripts and to Melanie Newton for very competent language assistance. We are also grateful for generous financial and administrative support from the Norwegian Research Council, especially the research project ‘Regulation, Control, and Auditing’. We also thank the Scandinavian Consortium of Organizational Research at Stanford University, the Rokkan Centre at the University of Bergen, the Department of Administration and Organizational Theory at the University of Bergen and the Department of Political Science at the University of Oslo.